FORMATION OF A CATEGORY SCIENTIFIC APPARATUS FOR THE ORGANIZATION OF INTERACTIVE LEARNING (Pedagogy of Higher and Secondary Education, 2010)
Problem offorming of category scientific vehicle which relates by organization of the interactive teaching is described in this article. Interpretation of concepts "interactive teaching", "interactive technologies", "interactive methods" is offered by author.
Keywords: interactive teaching; interactive technologies; interactive methods